Indigenous perspectives on gender, power and climate-related displacement - Pentlow, S (Refugee Studies Centre, University of Oxford, 2020)
Across the Greater Mekong subregion, Indigenous Peoples are employing a range of strategies to respond to the effects of climate change and climate-related displacement.